Caregiving, intellectual disability, and dementia: Report of the Summit Workgroup on Caregiving and Intellectual and Developmental Disabilities. Issue 1 (9th July 2018) - Heller, Tamar; Scott, Haleigh M.; Janicki, Matthew P.; ,; Heller, Tamar; Esbensen, Anna; Fazio, Sam; Yoshizaki‐Gibbons, Hailee; Hartley, Dean H.; Janicki, Matthew P.; Jokinen, Nancy; Kallmyer, Beth; et al.
Abstract: Introduction: A specially commissioned working group produced a report on caregiving, intellectual and developmental disabilities (IDDs), and dementia for the National Institutes of Health–located National Research Summit on Care, Services, and Supports for Persons with Dementia and Their Caregivers. Methods: Experts in caregiving, dementia, and IDDs examined the current state of research, policy, and practice related to caregiving and supports; identified the similarities and dissimilarities between IDD‐related care and services and the general population affected by dementia; and considered how these findings might contribute to the conversation on developing a dementia care research and services development agenda. Results: Five major areas related to programs and caregiving were assessed: (1) challenges of dementia; (2) family caregiving interventions; (3) supportive care settings; (4) effects of diversity; and (5) bridging service networks of aging and disability. Discussion: Recommendations included increasing supports for caregivers of adults with IDDs and dementia; increasing research on community living settings and including caregivers of persons with IDDs in dementia research; acknowledging cultural values and practice diversity in caregiving; increasing screening for dementia and raising awareness; and leveraging integration of aging and disability networks.